The Implementation of Politeness Strategies in Showing Disagreement Among the Communicative Members - Anis 'Azzah; Januarius Mujiyanto (English Education Journal, 2023)
Politeness is an essential aspect of interlanguage pragmatic study used to create a harmonious relationship among people who engage in specific interactions. Politeness is implemented differently in showing disagreement regardless of cultural background. This study was used to analyze the implementation of politeness strategies in showing disagreement by the students. In this study, the researchers applied descriptive qualitative research. The subjects in this study were 20 students, all non-native speakers, who joined the CEC club at UIN Salatiga. The data was taken from the students’ utterances of the politeness strategies used to show disagreement. Also, the data was analyzed using the theory of politeness strategies by Brown and Levinson (1987) In collecting the data, the researchers used a discourse completion test (DCT) questionnaire, which gave 5 (five) topics. The results showed that the students applied all politeness strategies with different percentages. Positive politeness is implemented for 73%, bald on record 18%, negative politeness for 5%, and off record 2%. Positive politeness is the most dominant strategy in showing disagreement. Besides, the sub-strategy in positive politeness also applied by the students are exaggerating, intensifying interest in the hearer, avoiding disagreement, presupposing, offering, being optimistic, including both the speaker and the hearer, giving or (asking for reason) and assuming or asserting reciprocity. In conclusion, politeness strategies are essential to convey a different opinion from the interlocutors.